DETERMINING THE FIRST PRIORITY OF THE FIRST ARSENAL LOCATION TO SUPPORT THE OPERATION OF THE INDONESIAN WARSHIP IN SAFETY OF THE EAST INDONESIAN SEA REGION WITH AHP METHODS - Muhammad Zulkifli; Cahyanto Cahyanto; Aris Tri Ika; Indra Agustian (JOURNAL ASRO, 2019)
Faced with conditions of life of the nation that continues to evolve into a multidimensional cover all areas of the life of the nation, then certainly required the development and deployment of the total potential and power of the nation effectively. Therefore it is the power that was developed to deal with these threats must also have the ability to multi-dimensional as well. Reality is always pushing to restructure the military concept of defense to become responsive and adaptable and tailored to the substance of the reforms in the defense. The main problem faced by Indonesia to develop a domestic defense industry is the inability of industry and education sectors to absorb the fundamental aspects of the Revolution in Military Affairs (RMA). This inability does not allow Indonesia to experience significant breakthroughs in the application of RMA. So with reference to the condition necessary to anticipate concrete steps in developing a systematic plan to build the defense industries are able to anticipate the revolution in military affairs. Among priorities at once by selecting the appropriate stages of the development plan which includes the development of Main Equipment Weapon System, Spatial Planning Area Defense, Civil Defense Development, and Spatial Structure of the Organization. And one of its efforts is the creation of the ability of military logistics support system effective and efficient and responsive, which in this case is the development of Arsenal's arsenal of weapons and ammunition in terms of both quality and quantity so that is always ready to face any condition of any contingency that would happen. Determining policy location Arsenal first location contains more choices in environmental issues multi-objective and multicriteria decision, then the model is proposed to be the appropriate methodology to accommodate the qualitative preference and priority-setting objectives/criteria for future development is to approach the Analytical Hierarchy Process (AHP). Principle of the AHP method is to break breaking a complex situation and unstructured, into its component parts, arranging these variables in a section or an order of hierarchy, giving numerical values to subjective considerations about the relative importance of each variable and analysis various considerations is to determine which variables have the highest priority and act to influence the outcome of the situation. From the results of the solution by using the AHP method showed that the first priority location determination Arsenal 1 in the eastern region is a factor analysis of logistics operations to support operations capabilities in the integrated logistics support system that effectively and efficiently. And the locations selected for Arsenal's first priority location is in the eastern region Lantamal Ambon.